Epidermal growth factor receptor mutation‐specific immunohistochemical antibodies in lung adenocarcinoma. Issue 6 (29th January 2014) - Allo, Ghassan; Bandarchi, Bizhan; Yanagawa, Naoki; Wang, Ami; Shih, Warren; Xu, Jing; Dalby, Morgan; Nitta, Hiroaki; To, Christine; Liu, Ni; Sykes, Jenna; Tsao, Ming S
<x xml:space="preserve">Abstract</x> Aims We investigated the sensitivity and specificity of two novel Epidermal growth factor receptor (EGFR) mutation‐specific antibodies in the detection of the most common EGFR mutations in lung adenocarcinoma. Methods and results A total of 241 resected lung adenocarcinoma specimens and six resected post‐neoadjuvant gefitinib adenocarcinomas were analysed for EGFR mutation using mass spectrometry, fragment analysis and direct PCR sequencing platforms. Tissue arrays and/or full sections of these cases were evaluated using immunohistochemistry with two novel antibodies (clones SP125 and SP111) and two previously reported antibodies (clones 43B2 and 6B6), specific for L858R or 15‐nucleotide exon‐19 deletion EGFR mutations. SP125 antibody detected EGFR L858R mutation with a sensitivity of 76% and positive predictive value of 73%. SP111 antibody stained the 15‐nucleotide EGFR exon‐19 deletions with a sensitivity of 83% and a positive predictive value of 94%. Pretreatment with gefitinib did not affect antibody performance. Full‐section immunohistochemical staining detected heterogeneous mutant EGFR proteins expression in tumours, and revealed L858R mutation in the non‐neoplastic bronchial epithelium adjacent to EGFR L858R‐carrying carcinomas in three of 16 (19%) cases. Conclusions Immunohistochemistry using EGFR mutant‐specific antibodies may be useful in shortening the diagnostic time of lung adenocarcinoma with most common EGFR mutations, especially in samples with low tumour cellularity.